2002
DOI: 10.1074/jbc.m202414200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning and Characterization of STAMP1, a Highly Prostate-specific Six Transmembrane Protein that Is Overexpressed in Prostate Cancer

Abstract: We have identified a novel gene, six transmembrane protein of prostate 1 (STAMP1), which is largely specific to prostate for expression and is predicted to code for a 490-amino acid six transmembrane protein. Using a form of STAMP1 labeled with green fluorescent protein in quantitative time-lapse and immunofluorescence confocal microscopy, we show that STAMP1 is localized to the Golgi complex, predominantly to the trans-Golgi network, and to the plasma membrane. STAMP1 also localizes to vesicular tubular struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
136
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 91 publications
(162 citation statements)
references
References 41 publications
10
136
0
2
Order By: Relevance
“…(27) STAMP1 is highly restricted to prostate for expression and is overexpressed in prostate cancer compared with benign prostate tissue. (28,29) STAMP1 expression is correlated with the presence of functional AR, even though it appears not to be androgen regulated. (28) STAMP2 has a more general tissue distribution.…”
Section: Stamp Familymentioning
confidence: 97%
See 2 more Smart Citations
“…(27) STAMP1 is highly restricted to prostate for expression and is overexpressed in prostate cancer compared with benign prostate tissue. (28,29) STAMP1 expression is correlated with the presence of functional AR, even though it appears not to be androgen regulated. (28) STAMP2 has a more general tissue distribution.…”
Section: Stamp Familymentioning
confidence: 97%
“…(28,29) STAMP1 expression is correlated with the presence of functional AR, even though it appears not to be androgen regulated. (28) STAMP2 has a more general tissue distribution. One of the major sites of its expression is the prostate, and it is strongly androgen regulated.…”
Section: Stamp Familymentioning
confidence: 97%
See 1 more Smart Citation
“…While searching for genes that are similar to STAMP1 (Korkmaz et al, 2002), we identified a BAC clone (GenBank Accession # AC003991) on human Chr7q21 that showed significant sequence similarity to STAMP1 cDNA ( Figure 1a). Computational exon/intron junction analysis of this locus and alignment of the full-length cDNA sequence revealed that there is a gene at this locus that is composed of five exons and four introns which is similar to STAMP1 cDNA along its whole sequence (Figure 1a).…”
Section: Isolation and Characterization Of The Stamp2 Gene And Mrnamentioning
confidence: 99%
“…While searching for genes that are differentially expressed during early stages of prostate cancer (Korkmaz et al, 2000), we have cloned a novel gene, six transmembrane protein of prostate 2 (STAMP2), named for its high sequence similarity to STAMP1, a highly prostate-enriched gene that is overexpressed in prostate cancer (Korkmaz et al, 2002). We show that STAMP2 is a highly androgen-regulated gene in androgen receptor-positive prostate cancer cells, but not in androgen receptor-negative cells.…”
Section: Introductionmentioning
confidence: 99%